2012
DOI: 10.1016/j.ocecoaman.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Wadden Sea tidal basins and the mediating role of the North Sea in ecological processes: scaling up of management?

Abstract: a b s t r a c tThe scale of human pressures on marine ecosystems gradually increased from local to global effects during the last centuries. Global warming, sea level rise and trans-oceanic spread of alien species are now or will be major drivers of ecological change in the Wadden Sea. Eutrophication may rank as a superregional effect as the organic matter turnover in the Wadden Sea is driven by import from the North Sea. These effects will not necessarily be uniform across the entire Wadden Sea. A major chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…By contrast, in deeper offshore regions, SPMC is lower and the flocs are looser and more organic. This general pattern of changing SPMC and composition from coast to open waters is typical for our research area, the German Bight (Eisma and Kalf, 1987), and is observed worldwide in estuaries (e.g., Fugate and Friedrichs, 2003) and across coastal seas (e.g., van der Lee et al, 2009). Since both SPMC and turbulence control the w s of cohesive material (Pejrup and Mikkelsen, 2010), it is likely that these cross-shore SPM gradients induce considerable spatial variability in w s and thus affect the transport and fate of SPM in coastal marine systems.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…By contrast, in deeper offshore regions, SPMC is lower and the flocs are looser and more organic. This general pattern of changing SPMC and composition from coast to open waters is typical for our research area, the German Bight (Eisma and Kalf, 1987), and is observed worldwide in estuaries (e.g., Fugate and Friedrichs, 2003) and across coastal seas (e.g., van der Lee et al, 2009). Since both SPMC and turbulence control the w s of cohesive material (Pejrup and Mikkelsen, 2010), it is likely that these cross-shore SPM gradients induce considerable spatial variability in w s and thus affect the transport and fate of SPM in coastal marine systems.…”
Section: Introductionsupporting
confidence: 65%
“…Applying the aforementioned concept of the transition zone as an off-coastal closing mechanism for nutrient cycling to the two contrasting German Wadden sea regions -East Frisian Wadden Sea and North Frisian Wadden Sea (particularly the Sylt-Rømø Bight) -may help to better understand regional differences in nutrient concentrations. Lower nutrient concentrations and thus lower eutrophication levels in the Sylt-Rømø Bight compared to the East Frisian Wadden Sea are regularly observed (van Beusekom et al, 2009). In this case, the maximal w s calculated in front of the Sylt-Rømø tidal inlet amounts only to 4 × 10 −4 m s −1 , about half the magnitude found off the other Wadden Sea regions.…”
Section: Spatial Biogeochemical Implications Of a Coastal Transition mentioning
confidence: 82%
See 3 more Smart Citations